Desenvolvimento relativo das partes do corpo de zebuínos de quatro raças - Jorge, André Mendes (2001)
Sixty-three intact males, 16 Gyr, 16 Guzerat, 15 Nellore and 16 'Mocho Tabapuã', averaging, respectively, 376.4, 357.6, 362.0 and 368.6kg initial live weight and twenty-four months of age, were used. The animals from each breed were divided into five groups (categories). One group was ramdomly assigned to immediate slaughter (AB), three groups were full-fed a ration containing 50% concentrate, dry matter basis until reaching the slaughter weights of 405, 450 and 500kg, respectively (group I, II and III). The fifth group was fed a restricted amount of the same ration to supply levels of protein and energy 15% above maintenance (AR). Each AR animal was slaughtered when an animal correspondent to group II reached the slaughter weight. At slaughter, the empty body weight was determined and the weight of internal organs were recorded. Regression equations of log content of internal organs, carcass and their tissues, as a function of log empty-body-weight (EBW), were fitted. The internal organs developed slower in relation to EBW.